INNOVATIVE APPROACHES AND THE ROLE OF CREATIVISM IN THE EDUCATION OF THE PERSONALITY OF AN INTELLECTUAL STUDENT IN A DIGITIZED EDUCATIONAL ENVIRONMENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes from a pedagogical point of view the influence of modern approaches on the effectiveness of modern education, as well as the practical significance of the content of the 4C approach components, describes the peculiarities of the intellectual formation of the student's personality, the environment in the acquisition of knowledge and skills, the ability to get out of situations based on new approaches to various processes encountered in everyday life using life experience, the ability to create creative information, the ability to choose the main ones and analyze them, and the effectiveness of assimilation.